Critique of the Realist Approach from a Historical-Conceptual Perspective within the Discipline - Madrigal, Alexander (2025)
The realistic approach in International Relations is often considered the discipline itself. From its origins, through various circumstances and theoretical debates, to the first quarter of the 21st century, its place and prestige, though questioned, remain in the practice of international politics and in the disciplinary epistemic community. However, from a historical perspective of the evolution of the discipline, in which its foundations are reviewed and questioned, such a place can be challenged. Thus, the objective of this article is to propose a critique using the methodology of conceptual history, reflective metatheory, and empirical analysis. The result is that realism in the discipline has been politically motivated and oriented, which calls into question it supposed scientific objectivity, as well as presenting sustained inconsistencies in its ontological and epistemological foundations; this hinders understanding, among other things, the problem of international change, being insufficient to analyze, for example, borders today. It is concluded that realism, while it can provide normative terms and reflections, is only a limited approach in a broader and richer crucible of theories, which is why academics are invited to explore multiple theoretical possibilities based on a historical, situated, and conceptual understanding of the discipline.